Seed Systems of Traditional African Vegetables in Eastern Africa: A Systematic Review - Ayenan, Mathieu A. T.; Aglinglo, Lys Amavi; Zohoungbogbo, Herbaud P. F.; N'Danikou, Sognigbe; Honfoga, Judith; Dinssa, Fekadu F.; Hanson, Peter; Afari-Sefa, Victor (Frontiers in Sustainable Food Systems, 2021)
Traditional African Vegetables (TAV) play an important role in the livelihoods, food and nutritional security of local populations. Access to high-quality seeds of improved varieties is a foundation for increasing crop productivity. TAV seed systems have received little attention. We systematically reviewed the literature to assess the sustainability (seed quality, availability, accessibility, affordability, and profitability of seed businesses) of TAV seed systems in Eastern Africa. The review revealed that the private sector mediated seed system (i.e., formal) offered higher potential for seed quality, and profitability for seed growers. The community-based seed system showed higher potential in ensuring a better access to seeds. The quality of TAV seeds was partially addressed in the studies with a focus on germination percentage and purity, which varied across systems, crops, and geography. While there was a trend of poorer seed quality in the informal system, seed quality in the formal and community-based systems was not necessarily better. The affordability of seed from the various systems (private sector mediated, community based and informal) needs further investigation. Because TAV seed systems are localized and differ significantly among and within countries, tailored interventions are required when promoting a given TAV seed system. We identified inter-regional gaps in TAV seed systems studies, with all the studies concentrated in Eastern Africa, mainly in Tanzania and Kenya. Filling these gaps will require more investment in other regions in sub-Saharan Africa to document existing initiatives or initiate interventions seeking to promote access to high-quality TAV seeds. This review sheds light on existing gaps in research on TAV seed systems to guide future interventions.